Brain Networks Implicated in Seasonal Affective Disorder: A Neuroimaging PET Study of the Serotonin Transporter - Nørgaard, Martin; Ganz, Melanie; Svarer, Claus; Fisher, Patrick M.; Churchill, Nathan W.; Beliveau, Vincent; Grady, Cheryl; Strother, Stephen C.; Knudsen, Gitte M. (Frontiers in Neuroscience, 2017)
Background Seasonal Affective Disorder (SAD) is a subtype of Major Depressive Disorder characterized by seasonally occurring depression that presents with symptoms such as hypersomnia and carbohydrate craving. The purpose of this study was to identify a 5-HTT brain network that accounts for the adaption to the environmental stressor of winter in females with the short 5-HTTLPR genotype, a specific subgroup previously reported to be at increased risk for developing SAD. Methods Nineteen females, either S' carriers (LG- and S-carriers) resilient to SAD (N=13, mean age 23.6±3.2 y) or S' carriers with SAD (N=6, mean age 23.7±2.4) were PET-scanned with [11C]DASB during both summer and winter seasons in randomized order, defined as a 12-week interval centered on summer or winter solstice. We used a multivariate Partial Least Squares approach, to identify a whole-brain pattern of 5-HTT levels that distinguished the brains of resilient females from females suffering from SAD. Results We identified a pattern of 5-HTT levels, distinguishing resilient females from those with SAD; it included the right superior frontal gyrus, brainstem, globus pallidus (bilaterally) and the left hippocampus. Across seasons, resilient female S’ carriers showed nominally higher 5-HTT levels in these regions compared to female S’ carriers with SAD, but the group difference was only significant in the winter. Female S’ carriers with SAD, in turn, displayed robustly increased 5-HTT levels in the ventral striatum (bilaterally), right orbitofrontal cortex, middle frontal gyrus (bilaterally), extending to the left supramarginal gyrus, left precentral gyrus and left postcentral gyrus during winter compared to resilient female S’ carriers. Limitations The study is preliminary and limited by small sample size in the SAD group (N = 6). Conclusions These findings provide novel exploratory evidence for a wintertime state-dependent difference in 5-HTT levels that may leave SAD females with the short 5-HTTLPR genotype more vulnerable to persistent stressors like winter. The preliminary findings provide additional insight into the neurobiological components through which the anatomical distribution of serotonergic discrepancies between individuals genetically predisposed to SAD, but with different phenotypic presentations during the environmental stressor of winter, may constitute a potential biomarker for both resilience and SAD.